In Vitro Evolution of Antibodies Inspired by In Vivo Evolution - Persson, Helena; Kirik, Ufuk; Thörnqvist, Linnea; Greiff, Lennart; Levander, Fredrik; Ohlin, Mats (Frontiers in Immunology, 2018)
In vitro generation of antibodies often requires variable domain sequence evolution to adapt the protein in terms of affinity, specificity, or developability. Such antibodies, including those that are of interest for clinical development, may have their origins in a diversity of immunoglobulin germline genes. Others and we have previously shown that antibodies of different origins tend to evolve along different, preferred trajectories. Apart from substitutions within the complementary determining regions, evolution may also, in a germline gene-origin defined manner, be focused to residues in the framework regions, and even to residues within the protein core, in many instances at a substantial distance from the antibody’s antigen-binding site. Examples of such germline origin-defined patterns of evolution are described. We propose that such germline gene-origin defined, preferred substitution patterns offer attractive alternatives that should be considered in efforts to evolve antibodies intended for therapeutic use with respect to appropriate affinity, specificity, and product developability. We also hypothesise that such germline gene-origin-defined in vitro evolution hold potential to result in products with limited immunogenicity, as similarly evolved antibodies will be parts of conventional, in vivo-generated antibody responses and thus are likely to have been seen by the immune system in the past.